Is screening for anal squamous intraepithelial lesions in women with genital human papillomavirus intraepithelial lesions necessary? - Vasconcelos Filho, Francisco Eugênio de; Eleutério Júnior, José; Dias, Bruno Hállan Meneses; Silva, Angélica Maria Holanda Pascoal da; Andrade, Ana Carolina Rodrigues de (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: There seems to be a fairly close relationship between genital and anal lesions associated with human papillomavirus (HPV) and with the pathogenesis of malignancies in such sites. Objective: This review seeks to analyze published papers that suggest the necessity for anal intraepithelial lesions screening in women with HPV genital intraepithelial lesions. Methods: A systematic review of original research published between 2001 and 2014 was performed in the databases PubMed, HighWire, Cochrane Library and Google Scholar. The keywords for the search were: “screening” or “early detection of cancer” and “anus” or “anus diseases” or “neoplasms anus” and “woman” or “women” and “HPV” or “DNA probes, HPV”. Results: 1,203 articles were selected in the first search. After the reviewers applied exclusion and inclusion criteria and analyzed the papers, 15 were selected to compose this review. Most of them showed higher rates of anal intraepithelial lesions in women with genital intraepithelial lesions than in regular women. We also found a correlation between genital neoplasms and anal infection by oncogenic HPV types and the role of the virus in the pathogenesis of anal cancer. Conclusion: Screening for anal lesions in women with HPV genital lesions should be indicated, and further studies are required to determine the best methods.